Molecular study of gene TP53 and immunohistochemical expression of p53 protein in the prognostic characteristics of patients with low-risk myelodysplastic syndrome - Fernando Barroso Duarte (2016)
The Myelodysplastic Syndrome (MDS) comprises a heterogeneous group of clonal diseases with complex pathogenesis, involving several phases and factors. TP53 gene mutations have been involved in progenitor cell homeostasis alterations with an impact on relevant functions in the development of neoplasms, such as genomic integrity maintenance, cell cycle regulation, apoptosis and inflammatory response. The aim of the study was to investigate the impact of the p53 protein expression, TP53 gene mutations and the R72P polymorphism on patients with low-risk MDS, associating them with clinical markers and prognostic scores and their applicability as an additional criterion to support hematopoietic stem cell transplantation (HSCT) indication. This is an analytical and prospective study involving 73 patients, of both genders, stratified as low risk, followed at the Outpatient Clinic of Walter CantÃdio University Hospital (HUWC) from February 2012 to August 2016. The p53 protein expression was assessed by immunohistochemistry, whereas the mutations and the R72P polymorphism were analyzed by direct sequencing. The statistical analysis used the GraphPad Prism 5.0 software and the significance level was set at p <0.05. Of the 73 patients who participated in the study, 20 (27.4%) were positive for the p53 protein expression. In the group with p53 expression, there was a significant reduction in hemoglobin and hematocrit levels, with increased frequency of fibrosis, hypercellularity and CD34 positivity in megakaryocytes. Of the 73 patients, 35 were screened for mutations in the TP53 gene and R72P polymorphism. Two mutations were identified in the study population, with a frequency of 5.7%. A nonsense mutation was identified for the first time in MDS in a female patient and a missense mutation, not yet reported in the literature, in a male patient. As for the R72P polymorphism, there was a predominance of the G allele and the GG genotype. All patients with "heterozygous" (CG) genotype were males. There was no association between mutations, polymorphism genotypes and clinical and prognostic parameters. During the study follow-up, two patients had indication for hematopoietic stem cell transplantation. One of them was positive for p53 in 40% of granulocytic precursors and died six months after the diagnosis. The second, who was negative for p53 expression and TP53 mutation, was submitted to HSCT and is in a stable condition. The results showed that p53 expression can influence clinical evolution and is associated with poor prognosis even in low-risk patients, reflecting the complexity of MDS and providing subsidies for further studies aiming to clarify the impact of the TP53 gene and the protein expression on the disease origin, progression and its therapeutic management, including HSCT.